Investigation into an efficient numerical modelling approach for estimating path-loss over variable terrain - Hussain, N. (Science Publishing Corporation Inc, 2018)
Different studies have been conducted for radio wave propagation in troposphere using different numerical modelling approaches. The most reliable approach is based on parabolic wave equation (PWE). The modelling of PWE is approached using different numerical schemes that include Split-step Fourier Transform Method (SSFM), Finite Element/Difference method and Wavelet based numerical method. The conventional Finite Element/Difference method are less accurate and/or computationally more expensive. While in comparison, split-step wavelet method (SSWM) is highly accurate and computationally very efficient. The SSWM has been previously used for modelling of PWE with smooth terrain. However, the real conditions are completely different as they contain variable terrain. The irregularities in surface of terrain have considerable influence because of reflection and diffraction on radio-wave propagation. In order to develop an effective communication system, a model that properly incorporates the reflection parameters from the variable terrain. In this research work, the SSWM is proposed for modelling of PWE for radio wave propagation over variable terrain. In SSWM, compactly supported wavelet of Daubechies 6 are used as bases. Obtained results accurately accounts the reflection from rough terrain surface and shows good agreement with SSFM. Â© 2018 Authors.